Transforming Political Divides: How Student Identities and Campus Contexts Shape Interpartisan Friendships - Alyssa N. Rockenbach; Tara D. Hudson (AERA Open, 2024)
Recent evidence suggests that only about 1 in 5 U.S. adults has a friend on the political “other side” (Dunn, 2020). Although these interpartisan friendships are uncommon, they play a critical role in catalyzing empathy, reducing prejudice, furthering justice, and even restoring democracy, as suggested by the theory of civic friendship (Goering, 2003; Kahane, 1999; Rawlins, 2009). In the present study, we drew on national data from the Interfaith Diversity Experiences and Attitudes Longitudinal Survey (IDEALS) to examine the personal and contextual factors that predict interpartisan friendship formation among 5,762 college students attending 118 higher education institutions in the United States. The findings revealed the constellation of individual, social, and institutional contributors to students’ capacities to reach across political differences in their friendships. We offer guidance for how college educators can support the development of these relationships that may open a path toward empathy and healing in our polarized society.